The Phenomenon of University Americanization: A Critical Review by Max Weber - Jarić, Isidora; Jovanović Ajzenhamer, Nataša (Etnoantropološki problemi / Issues in Ethnology and Anthropology, 2021)
The paper discusses the phenomenon of Americanization of European universities in a historical perspective, referring to the critical comparison of higher education in Germany and the United States, conceived by Max Weber after the experience of his stay at American universities in 1904. In accordance with the subject and goal, the paper is divided into several thematic units that include the historical context of European university development, defining the research question, the historical and theoretical context (his trip to the International Congress of Arts and Sciences in St. Louis and defining two of Weber’s key theoretical concepts (rationalization and bureaucratization) which are necessary for understanding his analysis of higher education), consideration of Weber’s most important work on this topic (Wissenschaft als Beruf), and presentation of the conclusions of our analysis. The paper provides an overview of Weber’s comparison of two university models: (a) the American model, which he sees as market-oriented, democratized and meritocratic, and (b) the German model, which he sees as critical, holistic and humanistic. Despite the prevailing opinion in modern Weberology that Weber was an apologist of the way in which American higher education works, in this paper we try to show that Weber in his deliberations offered a far more balanced view of the situation at universities in the two countries (United States and Germany), and that he managed to show different aspects, i.e. the advantages and disadvantages of these two, in many respects different, models of higher education and academic communities derived from them. Although the paper deals with a part of Max Weber’s legacy and in that sense with a discussion that is part of the history of sociological ideas, the basic ideas that Weber argues in it have not lost their relevance in contemporary discussions on higher education reform in Europe.